Dissimilation of Carbon Monoxide to Acetic Acid by Glucose-Limited Cultures of Clostridium thermoaceticum - Martin, Douglas R. (1985)
Clostridium thermoaceticum was cultivated in glucose-limited media, and the dissimilation of CO to acetic acid was evaluated. We found that cultures catalyzed the rapid dissimilation of CO to acetic acid and CO(2), with the stoichiometry obtained for conversion approximating that predicted from the following reaction: 4CO + 2H(2)O → CH(3)CO(2)H + 2CO(2). Growing cultures formed approximately 50 mmol (3 g) of CO-derived acetic acid per liter of culture, with the rate of maximal consumption approximating 9.1 mmol of CO consumed/h per liter of culture. In contrast, resting cells were found not to dissimilate CO to acetic acid. (14)CO was incorporated, with equal distribution between the carboxyl and methyl carbons of acetic acid when the initial cultivation gas phase was 100% CO, whereas (14)CO(2) preferentially entered the carboxyl carbon when the initial gas phase was 100% CO(2). Significantly, in the presence of saturating levels of CO, (14)CO(2) preferentially entered the methyl carbon, whereas saturating levels of CO(2) yielded (14)CO-derived labeling predominantly in the carboxyl carbon. These findings are discussed in relation to the path of carbon flow to acetic acid.